2022
DOI: 10.3389/fonc.2022.903059
|View full text |Cite
|
Sign up to set email alerts
|

Low-Intensity Focused Ultrasound Technique in Glioblastoma Multiforme Treatment

Abstract: Glioblastoma is one of the central nervous system most aggressive and lethal cancers with poor overall survival rate. Systemic treatment of glioblastoma remains the most challenging aspect due to the low permeability of the blood-brain barrier (BBB) and blood-tumor barrier (BTB), limiting therapeutics extravasation mainly in the core tumor as well as in its surrounding invading areas. It is now possible to overcome these barriers by using low-intensity focused ultrasound (LIFU) together with intravenously admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 118 publications
0
15
0
Order By: Relevance
“…However, effective and safe strategies remain limited. As a safe and non‐invasive approach, LIPUS has shown great potential in tissue repair and resolution of inflammation in various diseases 32–35 . Of note, the therapeutic effects of LIPUS on cardiovascular diseases have been reported in recent years 10–14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, effective and safe strategies remain limited. As a safe and non‐invasive approach, LIPUS has shown great potential in tissue repair and resolution of inflammation in various diseases 32–35 . Of note, the therapeutic effects of LIPUS on cardiovascular diseases have been reported in recent years 10–14 .…”
Section: Discussionmentioning
confidence: 99%
“…However, other proposed options include FITC-Dextran, Trypan blue, Nile blue, and sodium fluorescein [ 28 34 ]. Because of the narrow and precise aperture of the converging LIFU wave, many different targeting methods have been developed to cover the entirety of the target tissue volume and associated areas [ 19 ]. This can be achieved using a grid system to target specific points that utilize the additive effect of merging waves to produce the intended therapeutic effect [ 35 38 ].…”
Section: Methodsmentioning
confidence: 99%
“…HIFU is a direct treatment approach that directly induces tissue necrosis ( Figure 1 ), while LIFU induces BBB disruption for a more effective administration of pharmaceutical treatments ( Figure 2 ) [ 17 , 18 ]. The mechanism of HIFU treatment of peripheral brain tumors is through thermoablation and mechanical destruction while the mechanism of LIFU treatment of brain tumors is through the induction of functional and mechanical changes to the BBB and blood tumor barriers [ 19 ].…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…The acoustic treatment consisted of 3 ms bursts, every 100 ms, over a period of one minute, with an estimated focal PNP in the brain of 0.8 MPa, taking into account skull transmission factor based on [ 33 ]. An AP of 0.8 MPa was chosen since it is a typical level used to permeabilize the BBB in brain tumors in preclinical and clinical trials [ 25 , 26 ]. The treatment was performed with an MR-compatible FUS transducer (1.5 MHz central frequency, diameter: 25 mm, focal depth: 20 mm, Imasonic, Voray-sur-l′Ognon, France) connected to a therapeutic programmable FUS generator (Image-Guided Therapy, Pessac, France).…”
Section: Methodsmentioning
confidence: 99%
“…Few studies have suggested that BBB opening by FUS may also cause the temporary down-expression of P-gp on vessel walls, the duration of which was dependent on acoustic pressure (AP). P-gp was shown to fully recover three days after FUS application at low AP (e.g., peak negative pressure—PNP of 0.5 MPa, in situ) [ 23 , 24 ] whereas, at a higher AP of 0.8 MPa (similar to levels used in brain tumors trials [ 25 , 26 ]), P-gp does not return to baseline after three days [ 24 ]. However, despite these early findings, very little is known about the joint dynamics of the FUS-induced regulation of efflux transporters expressed at the BBB, and more data are needed to compare the dynamics of the expression of P-gp and BCRP over a longer time after FUS.…”
Section: Introductionmentioning
confidence: 99%